Health Waste Management: case study in municipal establishments of Pelotas, South Brazil - Alves, Simone Colvara; Gonçalves, Fernanda Medeiros; Monterosso, Edson Plá; Godecke, Marcos Vinicius (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
Among the health services waste (RSS), it’s possible to attribute some concern in the infective ones since they represent environmental and human contamination risks by inadequate management. With this sensitive aspect, this paper compares real situations experienced by local public health units in the city of Pelotas / RS (South of Brazil) with the recommendations in the Brazilian rules and laws, also showing the pre-operational phase of the treatment unit for this kind of waste. The methodology included bibliographical and documentary research, and field visits complemented by interviews with municipal employees involved in waste management. As a result, when comparing the current situation with the desired, problems that require corrective actions were found, like environmental education programs for stakeholders in relation to this management. Regarding the treatment unit, the study shows some aspects for the operation of an autoclave system.